Speech recovery and language plasticity can be facilitated by Sensori-Motor Fusion training in chronic non-fluent aphasia. A case report study. (3rd July 2018) - Haldin, Célise; Acher, Audrey; Kauffmann, Louise; Hueber, Thomas; Cousin, Emilie; Badin, Pierre; Perrier, Pascal; Fabre, Diandra; Perennou, Dominic; Detante, Olivier; Jaillard, Assia; Lœvenbruck, Hélène; et al.
ABSTRACT: The rehabilitation of speech disorders benefits from providing visual information which may improve speech motor plans in patients. We tested the proof of concept of a rehabilitation method (Sensori-Motor Fusion, SMF; Ultraspeech player) in one post-stroke patient presenting chronic non-fluent aphasia. SMF allows visualisation by the patient of target tongue and lips movements using high-speed ultrasound and video imaging. This can improve the patient's awareness of his/her own lingual and labial movements, which can, in turn, improve the representation of articulatory movements and increase the ability to coordinate and combine articulatory gestures. The auditory and oro-sensory feedback received by the patient as a result of his/her own pronunciation can be integrated with the target articulatory movements they watch. Thus, this method is founded on sensorimotor integration during speech. The SMF effect on this patient was assessed through qualitative comparison of language scores and quantitative analysis of acoustic parameters measured in a speech production task, before and after rehabilitation. We also investigated cerebral patterns of language reorganisation for rhyme detection and syllable repetition, to evaluate the influence of SMF on phonological-phonetic processes. Our results showed that SMF had a beneficial effect on this patient who qualitatively improved in naming, reading, word repetition and rhyme judgment tasks. Quantitative measurements of acoustic parameters indicate that the patient's production of vowels and syllables also improved. Compared with pre-SMF, the fMRI data in the post-SMF session revealed the activation of cerebral regions related to articulatory, auditory and somatosensory processes, which were expected to be recruited by SMF. We discuss neurocognitive and linguistic mechanisms which may explain speech improvement after SMF, as well as the advantages of using this speech rehabilitation method.